The second-tier status of fragile X syndrome testing for unexplained intellectual disability/global developmental delay in the era of next-generation sequencing - Wen Zhang; Wen Zhang; Wen Zhang; Dong Li; Dong Li; Dong Li; Nan Pang; Nan Pang; Nan Pang; Li Jiang; Baomin Li; Fanghua Ye; et al. (Frontiers Media S.A., 2022)
ObjectiveAlthough many unexplained intellectual disability/global developmental delay (ID/GDD) individuals have benefited from the excellent detection yield of copy number variations and next-generation sequencing testing, many individuals still who suffer from ID/GDD of unexplained etiology. In this study, we investigated the applicability of fragile X syndrome (FXS) testing in unexplained ID/GDD individuals with negative or absent genetic testing.MethodsIn this study, we used the triplet repeat primed polymerase chain reaction to evaluate the value and application of fragile X testing in unexplained ID/GDD individuals with negative or absent genetic testing (n = 681) from three hospitals.ResultsOf the 681 ID/GDD individuals with negative or absent genetic testing results detected by FXS testing, 12 men and one woman were positive. This corresponded to a diagnostic yield of 1.9% for FXS testing in our cohort. All FXS individuals had either a family history of ID/GDD or suggestive clinical features. The detection yield of FXS testing in ID/GDD individuals who completed genetic testing (2.70%, 12/438) was significantly higher than in individuals without any genetic testing (0.40%, 1/243).ConclusionsThis is the first report of FXS testing in ID/GDD individuals who lacked previous genetic testing, which promotes standardization of the FXS diagnostic process. These results highlight the utility of FXS testing of unexplained ID/GDD individuals with negative results from standard genetic testing. In the era of next-generation sequencing, FXS testing is more suitable as a second-tier choice and provides clinicians and geneticists with auxiliary references for tracing the etiology of ID/GDD.